Polska księgarnia w Petersburgu. Przyczynek do opisu polskiego ruchu wydawniczego na przełomie XIX i XX wieku - Kwiatkowska, Magdalena (Acta Universitatis Lodziensis. Folia Librorum, 2014)
The article concerns Polish Bookstore in Petersburg, existing in years 1879/1880-1918/1920. Within 40 years of bookselling and publishing the company changed hands and name several times. The publishing house was founded in 1879 in Warsaw by printer and publisher Gratian Unger (1853-1911) who remained its owner until 1883. In the years 1883-1886 it was owned by writer and journalist Henry Gliński, followed by Erasmus Piltz, co-founder and editor of the St. Petersburg magazine „Kraj” (1882-1909). In 1893 the company was taken over by Kazimierz Grendyszyński and in 1903 – by Polska Spółka Udziałowa [Polish Shareholding Company], on behalf of which the company was managed by Ferdynand M. Heidenreich (d. 1922). This article aims to organize the fractional information available in historical sources and publications of a biographical character. Based on bibliographic sources an attempt has been made to describe the publishing repertoire of Polish Bookshop in St. Petersburg up to year 1903 and the attitude of the Russian censorship towards it.